2013
DOI: 10.1158/1078-0432.ccr-12-3443
|View full text |Cite
|
Sign up to set email alerts
|

Serum Insulin-like Growth Factor-I Level Is an Independent Predictor of Recurrence and Survival in Early Hepatocellular Carcinoma: A Prospective Cohort Study

Abstract: Purpose: Insulin-like growth factor-I (IGF-I) reflects hepatic synthetic function and plays an important role in the development and progression of various cancers. In this study, we investigated whether pretreatment serum IGF-I levels predict time-to-recurrence (TTR) and overall survival (OS) in patients with early-stage hepatocellular carcinoma after curative treatment.Experimental Design: Consecutive patients with hepatocellular carcinoma who had undergone surgical resection, radiofrequency ablation, or per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…The liver, which is crucial in whole-body metabolic homeostasis, has been shown to participate in causing skeletal muscle wasting when compromised (Anand, 2017;Bhanji et al, 2017;De Bandt et al, 2018). Two hepatokines known to play a role in skeletal muscle homeostasis and pathogenesis of multiple diseases, including cancer cachexia, are the anabolic factor IGF1 and the catabolic factor IL6 (Song et al, 2013;Attard-Montalto et al, 1998;Bonetto et al, 2013;Costelli et al, 2006;Cho et al, 2013;Huber et al, 2018). The data presented in the current study support the notion that formation of LM, as occurring in CRC, may further perturb the hepatic production of IGF1 and IL6, thus exacerbating the potential for muscle wasting (Norris et al, 2014;Bonetto et al, 2012Bonetto et al, , 2011Ueda et al, 1994;Baltgalvis et al, 2009;White et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The liver, which is crucial in whole-body metabolic homeostasis, has been shown to participate in causing skeletal muscle wasting when compromised (Anand, 2017;Bhanji et al, 2017;De Bandt et al, 2018). Two hepatokines known to play a role in skeletal muscle homeostasis and pathogenesis of multiple diseases, including cancer cachexia, are the anabolic factor IGF1 and the catabolic factor IL6 (Song et al, 2013;Attard-Montalto et al, 1998;Bonetto et al, 2013;Costelli et al, 2006;Cho et al, 2013;Huber et al, 2018). The data presented in the current study support the notion that formation of LM, as occurring in CRC, may further perturb the hepatic production of IGF1 and IL6, thus exacerbating the potential for muscle wasting (Norris et al, 2014;Bonetto et al, 2012Bonetto et al, , 2011Ueda et al, 1994;Baltgalvis et al, 2009;White et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…[30–33] Furthermore, other studies suggested that lower plasma levels of IGF-1 were strongly associated with more advanced HCC parameters. [3436] Since HCC cells suppress normal hepatic function by replacing normal hepatocytes, advanced HCC might reduce IGF-1 synthesis to a greater extent than early HCC. In fact, our study showed that lower levels of serum IGF-1 were significantly related to more advanced AJCC stages.…”
Section: Discussionmentioning
confidence: 99%
“…The insulin-like growth factor (IGF) signaling pathway is associated with HCC cell growth and is important during the development and progression of HCC (5). IGF-I, IGF-II and their corresponding receptors mediate the biological functions of the IGF signaling pathway through the activation of the mitogen-activated protein kinase signaling pathway, which is involved in cell growth and metabolism (6,7).…”
Section: Introductionmentioning
confidence: 99%